Effects of asymmetric load bench press offset training on muscle activation levels and exercise-induced fatigue in collegiate bodybuilders - Yan, Bin; Yao, Siqi; Zhang, Junjie; Li, Chunwei; Han, Tongxin; Hu, Qiushi; Lv, Kai (Frontiers in Physiology, 2025)
ObjectiveThis study systematically investigated the effects of graded asymmetric load bench press offset training on muscle activation patterns, exercise-induced fatigue, and movement performance in bodybuilders.MethodsTen male athletes (age: 24.20 ± 1.91 years; 1 R M bench press: 120.00 ± 14.66 kg) underwent randomized crossover trials with 0% (symmetrical), 2%, 4%, and 6% asymmetric load interventions (70% 1 R M total load). Surface electromyography (sEMG) quantified activation levels of pectoralis major (PM), anterior deltoid (AD), triceps brachii (TB), and external oblique (EO), while barbell kinematics, blood lactate, and heart rate were analyzed to assess fatigue.ResultKey findings revealed significant interlimb asymmetry under symmetrical loading, with dominant-side PM (51 ± 6.82 vs 35 ± 5.32 MVIC%, p = 0.009) and AD (48.2 ± 5.05 vs 32.6 ± 9.21 MVIC%, p = 0.038) exhibiting higher activation than the non-dominant side. Asymmetric loading effectively mitigated this imbalance: 6% intervention increased non-dominant PM (54.4% ± 8.46% vs 0%: 35 ± 5.32 MVIC%, p = 0.035) and AD activation (52.3% ± 12.7% vs 0%: 32.6 ± 9.21 MVIC%, p = 0.022), but triggered compensatory EO recruitment (31.1% ± 12.3% vs 0%: 12.8 ± 3.34 MVIC%, p < 0.001). Performance metrics declined progressively with higher asymmetry: 6% loading reduced barbell velocity (MV: 0.28% ± 0.03% vs 0%: 0.38 ± 0.04 m/s, p < 0.001), repetitions (6.63% ± 2.40% vs 0%: 13.90 ± 2.52, p < 0.001), and power (MP: 357% ± 43% vs 0%: 437 ± 53.70 W, p = 0.009). Physiological fatigue markers intensified at 6% asymmetry, evidenced by elevated post-exercise blood lactate (7.42% ± 1.59% vs 0%: 9.88 ± 0.75 mmol/L, p = 0.003) and prolonged heart rate recovery.ConclusionThe study identifies 2%–4% asymmetric loading as optimal for enhancing non-dominant muscle activation while minimizing fatigue, whereas 6% interventions induce core compensation and performance deterioration. These findings establish evidence-based thresholds for precision training protocols, addressing interlimb asymmetry while balancing neuromuscular efficacy and physiological strain. Methodological innovations include multidimensional analysis of biomechanical, electromyographic, and physiological responses, advancing the understanding of neuromuscular coordination in asymmetric resistance training.